THE APPLICATION OF THE TEAM GAME TOURNAMENT (TGT) LEARNING MODEL IN INCREASING STUDENT INTEREST IN LEARNING - Adiyono, Adiyono; Umami, Fitriahul; Rahayu, Arum Putri (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This study aims to determine how the application of Teams Game Tournament learning increases the interest in learning class VIIIC students in Fiqh subjects at MTs. Al-Ihsan Tanah Grogot, and to find out whether, by applying Teams Game Tournament, learning can increase the interest in learning class VIIIC students in Fiqh subjects at MTs. Al-Ihsan Tanah Grogot. This study used a class action research design (PTK) with 2 cycles. Each cycle consists of planning stages, implementation of actions, observation and evaluation, as well as analysis and reflection. The research subjects were students of class VIIIC MTs. Al-Ihsan Tanah Grogot with a total of 39 students, observation of student activities with teachers, interest questionnaires, data analyzed by percentage techniques. The results showed that the application of Teams Game Tournament learning can increase students' interest in learning. The results of student interest in learning increased from the category of sufficient 18.91%, good 67.56%, very good 13.51% in cycle I to the category of sufficient 5.40%, good 54.05%, and very good 40.54% in cycle II. Thus the interest of students in class VIIIC MTs.Al-Ihsan Tanah Grogot in Fiqh subjects increased well after the application of Teams Game Tournament learning.